2019
DOI: 10.1016/j.celrep.2019.01.050
|View full text |Cite
|
Sign up to set email alerts
|

CBX7 Induces Self-Renewal of Human Normal and Malignant Hematopoietic Stem and Progenitor Cells by Canonical and Non-canonical Interactions

Abstract: Highlights d CBX7 regulates self-renewal of human primitive normal and leukemic cells d CBX7 binds SETDB1 and its inhibition induces differentiation of AML

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Furthermore, CBX7 (part of the polycomb repressive complex) was one of the top genes expressed by cluster 6 macrophages. CBX7 regulates HSC self-renewal and its downregulation induces macrophage differentiation (Jung et al, 2019;Klauke et al, 2013). Overall, these findings suggest that cluster 6 represents a transitional macrophage stage before terminal differentiation into mature lung macrophages.…”
Section: Extravascular Hla-dr Hi Monocytes Represent a Cellular Intermediate In Human Lung Macrophage Developmentmentioning
confidence: 66%
“…Furthermore, CBX7 (part of the polycomb repressive complex) was one of the top genes expressed by cluster 6 macrophages. CBX7 regulates HSC self-renewal and its downregulation induces macrophage differentiation (Jung et al, 2019;Klauke et al, 2013). Overall, these findings suggest that cluster 6 represents a transitional macrophage stage before terminal differentiation into mature lung macrophages.…”
Section: Extravascular Hla-dr Hi Monocytes Represent a Cellular Intermediate In Human Lung Macrophage Developmentmentioning
confidence: 66%
“…Downregulation of CBX7 is associated with HCC progression and poor prognosis in patients with HCC 21 . Moreover, CBX7 was found to induce self-renewal of malignant hematopoietic stem and progenitor cells 22 . However, several studies have shown that CBX7 could be an oncogene in multiple types of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Federico et al found that CBX7 and Protein Arginine Methyltransferase 1 (PRMT1) complex is critical for PRMT1 and for the expression of E-cadherin, a crucial hallmark of EMT [28]. Jung et al demonstrated that CBX7 act as a crucial regulator that induces human malignant hematopoietic stem and progenitor cells by noncanonical and canonical interactions and higher expression of CBX7 can also inhibit proliferation and promoted differentiation in acute myeloid leukemia, revealing therapeutic possibilities for leukemia [29]. Consistently, the present study revealed that CBX7 expression was related to OS in CESC, and the potential mechanism may be correlated with the biosynthesis of unsaturated fatty acids and O-glycan, protein export, glyoxylate and dicarboxylate metabolism, glycosaminoglycan biosynthesis-chondroitin sulfate, one carbon pool by folate and the nod-like receptor signaling pathway, as identi ed by GSEA.…”
Section: Discussionmentioning
confidence: 99%